2020
DOI: 10.1021/acsabm.0c00073
|View full text |Cite
|
Sign up to set email alerts
|

DNA Carbon-Nanodots based Electrochemical Biosensor for Detection of Mutagenic Nitrosamines

Abstract: Mutagenic and Carcinogenic substances are a threat to any living organism, and its detection is of paramount importance. In this work, we fabricate for the first time a DNA-carbon dots based electrochemical biosensor for sensitive and selective detection of mutagenic nitrosamines like N-nitrosodimethylamine (NDMA) and N-nitrosodiethanolamine (NDEA). At first, on the glassy carbon electrode (GCE), chitosan carbon dot was deposited, then, DNA was electro-statically immobilizing on the surface of carbon dots to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 33 publications
0
22
0
1
Order By: Relevance
“…Carbon quantum dots have been used in conjunction with DNA as a biorecognition element through drop-casting [51] due to their high surface area and multiple feasible binding sites. Majumdar et al [50] reported this using carbon quantum dots from chitosan modified with DNA for the detection of mutagenic nitrosamines N-nitrosodimethylamine (NDMA) and N-nitrosodiethanolamine (NDEA). This is achieved through the drop-casting of the chitosan carbon dots onto a GCE followed by drop-casting of DNA (Fig.…”
Section: Carbon-based Quantum Dots (Cqds)-based Biosensorsmentioning
confidence: 99%
“…Carbon quantum dots have been used in conjunction with DNA as a biorecognition element through drop-casting [51] due to their high surface area and multiple feasible binding sites. Majumdar et al [50] reported this using carbon quantum dots from chitosan modified with DNA for the detection of mutagenic nitrosamines N-nitrosodimethylamine (NDMA) and N-nitrosodiethanolamine (NDEA). This is achieved through the drop-casting of the chitosan carbon dots onto a GCE followed by drop-casting of DNA (Fig.…”
Section: Carbon-based Quantum Dots (Cqds)-based Biosensorsmentioning
confidence: 99%
“…Carbon dot–based DNA nanosensor has been used for detection of mutagenic nitrosamines, namely N -nitrosodimethylamine and N -nitrosodiethanolamine. Chitosan carbon dot–modified glassy carbon electrode immobilized with DNA undergoes change in differential pulse voltammetry peak current in presence of nitrosamines [ 132 ] (Fig. 8 ).…”
Section: Detection Of Other Toxic Pollutantsmentioning
confidence: 99%
“…8 Schematic representation of the process of fabricating modified electrode and subsequent detection of nitrosamine. Reproduced with permission from Majumdar et al, American Chemical Society [ 132 ] …”
Section: Detection Of Other Toxic Pollutantsmentioning
confidence: 99%
“…Majumdar等 [104] 制造了基于DNA-碳点的电化学 [38] . 图 13 用于腺苷检测的化学发光传感器的检测机制 [101] (网 络版彩图) Figure 13 Detection mechanism of chemiluminescence sensor for adenosine detection [101] (color online).…”
Section: 其他利用Cds增加其检测效能的生物传感器unclassified
“…参考文献 图 16 修饰电极的制作过程和亚硝胺的后续检测 [104] (网络 版彩图) Figure 16 The manufacturing process of the modified electrode and the subsequent detection of nitrosamine [104] (color online).…”
Section: 领域上已呈现出光明的应用前景mentioning
confidence: 99%